Multimodal single‐cell analysis reveals distinct radioresistant stem‐like and progenitor cell populations in murine glioma. Issue 12 (4th July 2020) - Alexander, Jes; LaPlant, Quincey C.; Pattwell, Siobhan S.; Szulzewsky, Frank; Cimino, Patrick J.; Caruso, Francesca P.; Pugliese, Pietro; Chen, Zhihong; Chardon, Florence; Hill, Andrew J.; Spurrell, Cailyn; Ahrendsen, Dakota; et al.
Abstract: Radiation therapy is part of the standard of care for gliomas and kills a subset of tumor cells, while also altering the tumor microenvironment. Tumor cells with stem‐like properties preferentially survive radiation and give rise to glioma recurrence. Various techniques for enriching and quantifying cells with stem‐like properties have been used, including the fluorescence activated cell sorting (FACS)‐based side population (SP) assay, which is a functional assay that enriches for stem‐like tumor cells. In these analyses, mouse models of glioma have been used to understand the biology of this disease and therapeutic responses, including the radiation response. We present combined SP analysis and single‐cell RNA sequencing of genetically‐engineered mouse models of glioma to show a time course of cellular response to radiation. We identify and characterize two distinct tumor cell populations that are inherently radioresistant and also distinct effects of radiation on immune cell populations within the tumor microenvironment. Main Points: Early after irradiation of murine glioma, FACS‐analysis shows stem‐like cells are enriched, and scRNA‐seq shows the radioresistant tumor cells are progenitors and stem‐like cells. Also, microglia and macrophage populations shift.